Perception of Faculty Regarding Proposed New Accreditation Norms by the National Assessment and Accreditation Council (NAAC) - Kumar, Atul; Gawande, Amol; Kristiawan, Muhammad; Finthariasari, Meilaty; Viona, Elsa; Tank, Mayank; Gupta, Daksh (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The National Education Policy (NEP) 2020 underscores the importance of accreditation and introduces the “National Accreditation Council” as its overarching body. The NEP envisions a 15-year phased approach, emphasising graded accreditation and institutional autonomy, aiming for all higher education establishments in India to evolve into self-governing entities focused on innovation and excellence. The National Assessment and Accreditation Council (NAAC) has formulated new guidelines, enabling universities and colleges operational for at least one academic year to apply for provisional accreditation. These guidelines intend to widen the scope of accreditation. Unlike the previous requirement that mandated institutions to be at least six years old or to have graduated two student cohorts for NAAC application, the new approach led to a limited number of institutions seeking accreditation due to low application rates. This article examines the viewpoints of 400 faculty members from Higher Educational Institutions in Maharashtra on whether the proposed norms will enhance the quality standards of these institutions. The faculty members collectively believe that the anticipated norms are unlikely to improve the existing quality standards of Higher Educational Institutions significantly.